2019
DOI: 10.3802/jgo.2019.30.e28
|View full text |Cite
|
Sign up to set email alerts
|

A multi-institutional analysis of sequential versus ‘sandwich’ adjuvant chemotherapy and radiotherapy for stage IIIC endometrial carcinoma

Abstract: ObjectiveTo analyze the outcomes of sequential or sandwich chemotherapy (ChT) and radiotherapy (RT) in patients with node-positive endometrial cancer (EC).MethodsData from 4 centers were collected retrospectively for 179 patients with stage IIIC EC treated with postoperative RT and ChT (paclitaxel and carboplatin). Patients were either treated with 6 cycles of ChT followed by RT (sequential arm; 96 patients) or with 3 cycles of ChT, RT, and an additional 3 cycles of ChT (sandwich arm; 83 patients). Prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…There is an ongoing debate about routine surgical staging with LN dissection or sampling in EC, especially after the introduction of molecular profiling. Yet, LN status as determined by either lymphadenectomy or SLN remains an important prognosticator for survival and guiding adjuvant treatment in the current ESMO-ESGO-ESTRO risk classification [5,[30][31][32][33]. The study of Ouldamer et al concluded, that even patients within the 'high-intermediate' risk group should receive systematic nodal staging for a significant better survival [34].…”
Section: Discussionmentioning
confidence: 99%
“…There is an ongoing debate about routine surgical staging with LN dissection or sampling in EC, especially after the introduction of molecular profiling. Yet, LN status as determined by either lymphadenectomy or SLN remains an important prognosticator for survival and guiding adjuvant treatment in the current ESMO-ESGO-ESTRO risk classification [5,[30][31][32][33]. The study of Ouldamer et al concluded, that even patients within the 'high-intermediate' risk group should receive systematic nodal staging for a significant better survival [34].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there was no article mentioned about the comparison between sandwich and concurrent CRTs. Similarly, Onal et al reported a superiority of sandwich CRT in PFS and OS, compared with sequential CRT or radiotherapy only [ 8 , 9 ]. The underlying mechanism explaining the finding about the superiority of sandwich CRT is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Young et al reported that positive lymph node metastasis was associated with worse PFS (HR = 3.37, p = 0.03) and OS (HR = 2.96, p = 0.04) in FIGO 1988 stage III EC patients [ 12 ]. Onal et al also found that paraaortic lymph node metastasis was a predictor for worse OS (HR = 2.01, 95% CI = 1.15–3.53, p = 0.02) compared with pelvic lymph node metastasis [ 9 ]. Thus, patients with paraaortic lymph node metastasis might be treated with a more intensive therapy to prevent EC recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 57% of all endometrial cancer cases are related to obesity or being overweight [3]. Although patients with early-stage endometrial cancer are efficaciously treated with surgery, with or without chemo-radiotherapy, resulting in five-year survival rates of 80-85% [4], these therapeutic options are limited in younger patients due to the desire to preserve fertility and in obese patients due to poor hormonal sensitivity and surgical outcomes and higher cost of surgical care [5]. Twenty percent to 30% of endometrial cancer patients are diagnosed with the late-stage disease 2 of 22 at the time of surgery, with an estimated five-year survival rate of 40-70% for stage III patients, and a very poor five-year survival of 0-10% for stage IV patients [6].…”
Section: Introductionmentioning
confidence: 99%